The Effect Of Transformational Leadership Style And Effectiveness On The Performance Of 212 Mart Citra Garden Store Employees, Gowa District - Dicky Zulkarnain Rona Gah; Andi Fajariansyah (Jurnal Economic Resource, 2022)
This study aims to analyze the effect of transformational, effectiveness, and employee performance at 212 Citra Garden Mart, Gowa Regency. This research was conducted in 212 Citra Garden with a population and sample of all employees totaling 35 people. Data was collected through the distribution of questionnaires and documentation. Data were analyzed. Validity test. reliability. Classical assumption test. Multiple Linear Regression Analysis and Coefficient of Determination (R2) using the SPSS application. The results showed that partially transformational leadership style and effectiveness positively affected employee performance at Citra Garden Mart 212, Gowa Regency.